Cultural intelligence and social distance among undergraduate students in clinical professions. (February 2022) - Segev, Ronen; Mor, Shira; Even-Zahav, Ronit; Neter, Efrat
Cultural competence, also known as cultural intelligence (CQ), is considered a necessary skill in the clinical professions and for resolving intergroup conflict, yet it has not been examined within the framework of the contact hypothesis. The aim of the present research is to extend CQ theory from management to the clinical professions and examine it in a context of intergroup conflict. The present study examined CQ and social distance among entering undergraduate majority (Jewish) and minority (Arab) students in clinical study domains, hypothesizing that CQ will be negatively associated with social distance towards outgroup members and that minority students will report higher CQ than majority students. First-year students ( N = 180) from diverse demographic and study domains (social work, nursing, behavioral sciences) were surveyed. The results reveal a novel negative association between CQ and outgroup social distance, and higher CQ among minority-group students. The finding that students from minority backgrounds were more receptive to intercultural exchange at the outset of their training suggests that CQ theory could be used in training and evaluation criteria of students entering clinical professional training.